Synergy between KPP Pratama Jakarta Menteng Satu and banks in tax collection through account blocking - Millatina, Desy; Cahyady, Yadhy (WIM Solusi Prima, 2025)
One of the tax collection actions is blocking the taxpayer's account. The Directorate General of Taxes (DGT) has the authority to access taxpayer financial information in collaboration with banking institutions. This study evaluates the synergy between KPP Pratama Jakarta Menteng Satu and banks in executing account-blocking actions and their contribution to the realization of revenue collection. This research adopts a qualitative methodology, utilizing literature reviews and interviews with the Examination, Assessment, and Collection section for primary data collection, while secondary data is gathered through documentation studies. The synergy between the Tax Office and banks is assessed based on the timeliness of the bank's response to requests and the successful execution of blocking actions on identified accounts. The findings indicate that the effectiveness of this synergy fluctuated over three consecutive years, ranging from ineffective to highly effective. Key obstacles include delayed bank responses, uncertainty regarding account information, discrepancies in customer data, and conflicting priorities between DGT and banks. These challenges have resulted in a consistently low contribution of account-blocking actions to annual collection revenue. Despite these limitations, account blocking remains a critical enforcement mechanism for pressuring taxpayers to settle outstanding arrears. This study underscores the need for enhanced coordination between DGT and banking institutions and improved data accuracy to optimize the effectiveness of account blocking and maximize its contribution to tax collection efforts.